Effect of irradiation with medium doses of high-energy electrons on the fluctuation conductivity of Y1Ba2Cu3O7–δ single crystals - Azarenkov, N.A.; Khadzhai, G.Ya.; Komisarov, A.O.; Gevorkyan, E.S.; Vovk, R.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2023)
The effect of medium doses (from 1019 to 1020 cm–2) of irradiation with fast electrons (energy, Е = 2.5 MeV) on the excess conductivity of optimally doped Y1Ba2Cu3O7–δ single crystals has been studied. It is shown that the irradiation with electrons leads to the significant expansion of the temperature interval for the existence of excess conductivity, thereby narrowing the region of the ρ(Т) linear dependence in the ab plane in the normal state. It has been established that at doses of 0 ≤ D ≤ 6.5·1019 cm–2, the value of the transverse coherence length ξс(0) increases with D by about 3 times and the 2D–3D crossover point shifts in temperature. In contrast to the case of irradiation with low doses (D ≤ 1019 cm–2), irradiation with medium doses leads to a nonmonotonic dependence of the transverse coherence length ξс(0) on the irradiation dose, with a characteristic maximum at D (7–8)·1019 cm–2, which may be related to the general suppression of superconducting characteristics.